Reverse Engineering Applied to the Teaching of Computer Aided Manufacturing - Núñez, Pedro José; Beamud González, Elena María; Rodríguez Salgado, David; García Plaza, Eustaquio; González González, Alfonso; Sanz-Calcedo, Justo García (Materials science forum, 2017)
One of the main shortcomings of individualized training in the use of computer aided design (CAD), and computer aided manufacturing (CAM) tools is that students lack a sound and broad understanding of the type of tools, and their specific and integrated applications in industrial manufacturing. This study aimed to design an integrated curricular training programme in computer aided tools for the design and manufacture of mechanical components based on reverse engineering techniques. By using real products that students can see and touch, a scanned copy is obtained for subsequent reconstruction into a virtual three-dimensional model using the software for optimizing the point cloud, meshing, and creating both the surface and solid. Once the virtual three-dimensional model has been obtained, it is exported to a solid modelling CAD (3D-CAD) software for modification according to the geometrical requirements. The next step is for students to manufacture a component using rapid prototyping techniques, which allow them to visualize, analyse, and inspect a component to optimize its design. The use of computer aided manufacturing software enables students to design and plan machining operations virtually to obtain a computer numeric control (CNC) program for the manufacture of a component with a CNC machine tool. Finally, students perform a quality control of the component by employing a range of measurement techniques. This training program is integrated into the subjects of the mechanical engineering degree, where students can work with these tools in line with an intergraded curriculum.